The regulation of antiviral activity of interferon epsilon - Zhao, Fu-Rong; Wang, Wei; Zheng, Qin; Zhang, Yan-Ge; Chen, Jianming (Frontiers in Microbiology, 2022)
Interferon epsilon (IFN-ε) is a type I IFN. Some biological properties has been identified in many species, such as antiproliferative, anti-tumor, and antiviral effects, of IFN-ε, which are much weaker than those of IFN-α, have also been revealed. It has been shown to play a role in mucosal immunity and bacterial infection and in the prevention of certain sexually transmitted diseases, such as human immunodeficiency virus (HIV). This paper reviews the known activity of IFN-ε, particularly in some viruses. In general, this review provides a better understanding of effective IFN-ε treatment in the future.